Microscopic Calculations of Low and Medium Energy Fission with the CoMD (Constrained Molecular Dynamics) Model - Vonta, N.; Souliotis, G. A.; Bonasera, A.; Veselsky, M. (HNPS Advances in Nuclear Physics, 2019)
The investigation of the mechanism of nuclear fission is a topic of current experimental and theoretical interest. In this work, we initiated a systematic study of low and intermediate energy fission calculations using the Constrained Molecular Dynami cs (CoMD) code. The code implements an effective interaction with a soft isoscalar part and with several forms of the density dependence of the nucleon symmetry potential. In addition, CoMD imposes a constraint in the phase space occupation for each nucleon restoring the Pauli principle at each time step of the evolution of the nuclear system. Proper choice of the surface parameter of the effective interaction has been made to describe fission. In this work, we present CoMD calculations for several proton- included fission reactions at low and intermediate energy and compare them with recent experimental data. We found that the CoMD code is able to describe the complicated many-body dynamics of the fission process especially for intermediate and higher-energy fission reactions. Proper adjustment of the parameters of the effective interaction and further improvements of the code are necessary to achieve a satisfactory quantitative description of low-energy fission where shell effects play a definitive role.